Biocompatibility and biodegradation of protein microparticle and film scaffolds made from kafirin (sorghum prolamin protein) subcutaneously implanted in rodent models. Issue 8 (29th December 2014) - Taylor, Janet; Anyango, Joseph O.; Potgieter, Marnie; Kallmeyer, Karlien; Naidoo, Vinny; Pepper, Michael S.; Taylor, John R. N.
Abstract Kafirin, the sorghum prolamin protein, like its maize homologue zein, can be made into microparticles and films and potentially used as a biomaterial. Zein has good bio‐ and cyto‐compatibility. Kafirin could be advantageous as it is more hydrophobic, more crosslinked, more slowly digested by mammalian proteases than zein and is non‐allergenic. The safety and biocompatibility of kafirin implants in two forms was determined in rodent models. One week post subcutaneous injection of kafirin microparticles (size 5‐µm diameter) in mice, chronic inflammation, abnormal red blood cells, and gross fibrin formation were observed. This chronic inflammatory response was possibly caused by the release of hydrolysis products such as glutamate during the degradation of the kafirin microparticles. In contrast, films made from kafirin microparticles (50‐µm thick, folded into 1 cm3) implanted in rats showed no abnormal inflammatory reactions and were only partially degraded by day 28. The slower degradation of the kafirin films was probably due to their far smaller surface area when compared to kafirin microparticles. Thus, kafirin films appear to have potential as a biomaterial. This study also raises awareness that the form of prolamin based biomaterials, (kafirin and zein) should be considered when assessing the safety of such materials. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2582–2590, 2015.